Complex Crystal Structure Determination of Hsp90N-NVP-AUY922 and In Vitro Anti-NSCLC Activity of NVP-AUY922 - He, Chun-Xia; Lv, You; Guo, Meng; Zhou, Huan; Qin, Wei; Zhao, Dong; Li, Hui-Jin; Xing, Lu; Zhou, Xin; Li, Peng-Quan; Yu, Feng; He, Jian-Hua; et al. (Frontiers in Oncology, 2022)
New targeted chemotherapy agents greatly improved five-year survival in NSCLC patients, but which were susceptible to drug resistance. NVP-AUY922, terminated in phase Ⅱ clinical trials, exhibited promising anti-NSCLC (non-small-cell lung cancer) activity targeting to Hsp90N (heat shock protein), which demonstrated advantages in overcoming drug resistance as a broad-spectrum anti-cancer target. It was expected to develop novel anti-NSCLC drugs to overcome drug resistance by the structural optimization of NVP-AUY922. However, the absence of high-resolution complex crystal structure of Hsp90N-NVP-AUY922 blocked the way. Herein, 1.59 Å-resolution complex crystal structure of Hsp90N-NVP-AUY922 (PDB ID 6LTI) was successfully determined by X-ray diffraction. Meanwhile, there was a strong binding capability between NVP-AUY922 and its target Hsp90N verified by TSA (ΔTm, -15.56±1.78 °C) and ITC (Kd, 5.10±2.10 nM). Results by the complex crystal structure, TSA and ITC verified that NVP-AUY922 well accommodated in the ATP-binding pocket of Hsp90N to disable the molecular chaperone activity of Hsp90. Therefore, NVP-AUY922 exhibited approving inhibitory activity on NSCLC cell line H1299 (IC50, 2.85±0.06 μM) by inhibiting cell proliferation, inducing cell cycle arrest and promoting cell apoptosis. At the basis of the complex crystal structure and molecular interaction analysis, thirty-two new NVP-AUY922 derivatives were further designed, and among which twenty-eight new ones display enhanced binding force with Hsp90N by molecular docking evaluation. The results would promote anti-NSCLC new drug development to overcome drug resistance based on the lead compound NVP-AUY922.